Konflik batin tokoh utama dalam cerpen laki-laki tua tanpa nama: analisis psikoanalisis freud - Faiz, Moh (Maliki Interdisciplinary Journal, 2026)
This study aims to examine the inner conflict of the main character in a short story through the perspective of Freud’s psychoanalysis with a focus on the dynamics of personality structure. The issues studied are related to psychological tension that arises due to the conflict between internal impulses and social pressures experienced by the character. The research uses a qualitative approach with a narrative study type that emphasizes an in-depth analysis of the inner experiences of the characters in the text. Data were collected through documentation techniques and intensive reading of short story texts, with the research subjects in the form of the main characters showing indications of complex psychological conflicts. Data analysis was carried out thematically by identifying the relationship between id, ego, and superego in forming inner conflicts. The results of the study show that inner conflict develops dynamically due to imbalances in personality structure, which gives rise to anxiety, self-defense mechanisms, and emotional outbursts as the peak of conflict. These findings confirm that inner conflict is not static, but rather an ongoing psychological process in narrative construction. The implications of this study strengthen the relevance of the psychoanalytic approach in literary studies and contribute to the interpretive understanding of the psychological dynamics of characters. This research also opens up opportunities for the development of similar studies in other literary works to expand the understanding of inner conflict in a more diverse context.